Dampak Pernikahan Beda Agama terhadap Perkembangan Iman Anak Usia Balita di Paroki Hati Kudus Tuhan Yesus Simo Boyolali - Agatha Lilis Pratiwi; Anselmus Joko Prayitno; Gregorius Daru Wijoyoko (Publisher STPKat, 2025)
As a multicultural country, Indonesia grows and develops with various cultural structures, ethnicities, religions and races. The diversity that occurs for a long time makes it possible for marriages with different religions to occur. Interfaith marriage in the Catholic Church is not allowed, but there is a dispensation so there are people who do it. As happened at the Sacred Heart of Jesus Simo Church, Boyolali, from the data for 2018-2023, there were 41 marriages and 9 of them were married to different religions (Cult Disparity). This phenomenon occurs due to several things including a lack of appreciation of faith, not enough socializing in the Church, pregnancy outside of marriage, a high sense of tolerance, many public schools in the village, places of worship that are close enough to allow the existence of many followers of other religions. The purpose of this research is to find out the nature of marriage of interfaith marriage couples, the application of children's faith education and the development of parents' faith from interfaith marriages. This research uses a descriptive qualitative method with interviews with informants. The results showed that the impact of interfaith marriage on the faith education of children under five is positive because since infancy they have been baptized in accordance with the nature of Catholic marriage. Based on the results of the study, each partner respects and supports the other's beliefs in the midst of differences. In educating children's faith in the golden age period, they can be baptized.